The Clinical Characteristics of ARDS in Children With Hematological Neoplasms - Zhang, Qiao; Hu, Wen-ting; Yin, Fan; Qian, Han; Wang, Ying; Li, Bi-ru; Qian, Juan; Tang, Yan-jing; Ning, Bo-tao (Frontiers in Pediatrics, 2021)
In order to explore the clinical characteristics of pediatric patients admitted to the pediatric intensive care unit (PICU) who suffered from hematological neoplasms complicated with acute respiratory distress syndrome (ARDS), we retrospectively analyzed 45 ARDS children with hematological neoplasms who were admitted to the PICU of Shanghai Children's Medical Center from January 1, 2014, to December 31, 2020. The 45 children were divided into a survival group and a non-survival group, a pulmonary ARDS group and an exogenous pulmonary ARDS group, and an agranulocytosis group and a non-agranulocytosis group, for statistical analysis. The main clinical manifestations were fever, cough, progressive dyspnea, and hypoxemia; 55.6% (25/45) of the children had multiple organ dysfunction syndrome (MODS). The overall mortality rate was 55.6% (25/45). The vasoactive inotropic score (VIS), pediatric critical illness scoring (PCIS), average fluid volume in the first 3 days and the first 7 days, and the incidence of MODS in the non-survival group were all significantly higher than those in the survival group (P < 0.05). However, total length of mechanical ventilation and length of hospital stay and PICU days in the non-survival group were significantly lower than those in the survival group (P < 0.05). The PCIS (OR = 0.832, P = 0.004) and the average fluid volume in the first 3 days (OR = 1.092, P = 0.025) were independent risk factors for predicting death. Children with exogenous pulmonary ARDS were more likely to have MODS than pulmonary ARDS (P < 0.05). The mean values of VIS, C-reactive protein (CRP), and procalcitonin (PCT) in children with exogenous pulmonary ARDS were also higher (P < 0.05). After multivariate analysis, PCT was independently related to exogenous pulmonary ARDS. The total length of hospital stay, peak inspiratory pressure (PIP), VIS, CRP, and PCT in the agranulocytosis group were significantly higher than those in the non-agranulocytosis group (P < 0.05). Last, CRP and PIP were independently related to agranulocytosis. In conclusion, children with hematological neoplasms complicated with ARDS had a high overall mortality and poor prognosis. Children complicated with MODS, positive fluid balance, and high VIS and PCIS scores were positively correlated with mortality. In particular, PCIS score and average fluid volume in the first 3 days were independent risk factors for predicting death. Children with exogenous pulmonary ARDS and children with agranulocytosis were in a severely infected status and more critically ill.